Challenges, Opportunities, and Strategies of Pentahelix Stakeholders in Realizing Sustainable Supply Chains in Indonesia - Setiawan, R. Beniadi (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The sustainable supply chain sector is increasingly becoming an important concern in Indonesia, especially amidst the threats of climate change, environmental degradation, and exploitation of natural resources. This study aims to identify the challenges, opportunities, and strategies faced by pentahelix stakeholders in realizing a sustainable supply chain in Indonesia. This study uses a qualitative method with a case study approach. The data collection technique in this study is through literature studies. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that efforts to realize a sustainable supply chain in Indonesia require strong collaboration between the government, academics, business, society, and the media. Pentahelix is ??the right strategy to ensure that each stakeholder plays its role optimally. By taking advantage of existing opportunities, such as increasing consumer demand for environmentally friendly products and strong government support and overcoming challenges through technological innovation and comprehensive policy development, Indonesia has great potential to become a leader in sustainable business practices at the global level.